IDENTIFIKASI ARTHROPODA HAMA DAN MUSUH ALAMI PADA GUDANG BERAS PERUM BULOG DAN GUDANG GABAH MITRA KERJA DI KABUPATEN JEMBER - Roza Anugraha Wiranata; Toto Himawan; Ludji Pantja Astuti (Jurnal HPT (Hama Penyakit Tumbuhan), 2013)
ABSTRACTThis research in order to identified pest Arthropods and natural enemies on Perum Bulog rice warehouse and Mitra Kerja rough rice warehouse in Jember Regency. The research was conducted in July 2011 to August 2011. Data collection using direct survey method by deriving rice and rough rice sampling on stapel, placement of traps in the rice and rough rice warehouse, and deriving scattered sample in the rice and rough rice warehouse. Arthropods that found then identified and counted the population in Pest Laboratory, Department of Pest and Plant Disease, Faculty of Agriculture, Brawijaya University, Malang. The results showed that in the rice warehouse found 17993 individual Arthropods thatincludes 2 classes, 8 orders, 13 families, and 16 species. At the rough ricewarehouse found 1170 individual Arthropods that includes 2 classes, 8 orders, 16 families, and 22 species.Keywords: Perum Bulog, Pest of Stored Products, UV Light Trap, Yellow StickyTrap